Advances in vitiligo: Update on therapeutic targets - Feng, Yifei; Lu, Yan (Frontiers in Immunology, 2022)
Vitiligo, whose treatment remains a serious concern and challenge, is an autoimmune skin disease characterized by patches of depigmentation. The increasing application of molecular-targeted therapy in skin diseases, such as psoriasis and systemic lupus erythematosus, has dramatically improved their condition. Besides, there is a favorable effect of repigmentation in the treatment of the above diseases combined with vitiligo, implying that molecular-targeted therapy may also have utility in vitiligo treatment. Recently, the role of cytokine and signaling pathways in vitiligo pathogenesis are increasingly recognized. Thus, investigations are underway targeting the molecules described above. In this paper, we present a synopsis of current practices in vitiligo treatment and introduce the improvement in identifying new molecular targets and applying molecular-targeted therapies, including those under development in vitiligo treatment, providing valuable insight into establishing further precision medicine for vitiligo patients.